INFEKSI Salmonella enteritidis PADA TELUR AYAM DAN MANUSIA SERTA RESISTENSINYA TERHADAP ANTIMIKROBA - Kusumaningsih, Anni; Sudarwanto, M (Research Center for Biology-Indonesian Institute of Sciences, 2011)
Salmonella enteritidis is one of pathogenic bacteria in chicken and human with re-emerging foodbome pathogen. Uncontrol use of antimicrobial drugs for the prevention and treatment of infectious diseases in chicken and human may lead to the development of antimicrobial resistance. Sampels of chicken eggs were collected from markets, layer farms, and grant parent stock farms. Sampels from human were anal swabs collected from hospitals and a laboratory of microbiology. Identification of bacteria was conducted by isolation and biotyping using selected media for Salmonella, while serotyping S. enteritidis was conducted with spesific 0 somatic (1, 9, and 12) and H flageIJa (m) antigen.Antimicrobial resistance tests were conducted by the standard diffusion method using antimicrobial disks.The results of isolation and identification of Salmonella show that 9 out of 122 (7.4%) sampels of layer eggs and 7 out of 23 (30.4%) sampels of embrioneted eggs were positive with Salmonella spp. The results of serotyping against S. enteritidis show that 7 out of 9 (77.0%) from layer eggs and 7 out of 7 (100.0%) from embrioneted eggs were positive with S. enteritidis.From the IS anal swabs of human were obtained 14 (93,3%) contain S. enteritidis.The antimicrobial resistance profiles of S. enteritidis isolated from layer eggs show high resistances to streptomycin (42.9%), neomycin (85.7%), doxicycline (64.3%), and ciprofloxacin (57,1%), whereas those S. enteritidis isolated from human show high resistances to streptomycin (50.0%), neomicyn (85.7%), tetracycline (42.9%), and doxicycline (42.9%).Multiple resistance profiles of S. enteritidis isolated from eggs were mostly to 2-3 antibiotics and those of S. enteritidis isolated from human were mostly to more than 5 antibiotics.